Pengaruh Promosi Penjualan, Persepsi Manfaat dan Persepsi Kemudahan terhadap Minat Menggunakan E-Wallet Shopeepay Pada Mahasiswa Universitas Singaperbangsa Karawang - Syukriyyah Syukriyyah; Karyaningsih Karyaningsih (Transformasi Manageria: Journal of Islamic Education Management, 2023)
This study aims to analyze the effect of sales promotion, perceived usefulness and perceived ease of use of interest in using shopeepay e-wallet in Singaperbangsa Karawang University students. This study uses a descriptive verification approach with quantitative methods, with the help of Microsoft Excel and SPSS software. Data collection in this study was carried out by distributing questionnaires via google form. The population in this study were all students of the University of Singaperbangsa Karawang 2021. The sample was taken using the probability sampling with the proportionate stratified random sampling technique, with a sample of 392 respondents. The test stages used are: validity test, reliability test, classical assumption test, multiple linear regression, hypothesis testing and coefficient of determination. The results of this study indicate that the variables of sales promotion, perceived usefulness and perceived ease of use partially have a positive effect on the interest in using shopeepay e-wallet in Singaperbangsa Karawang University students with 23.4%, 19% and 27.2% respectively. Meanwhile, simultaneously, sales promotion variables, perceived usefulness and perceived ease of use, affect the interest in using shopeepay e-wallet among Singaperbangsa Karawang University students. Together, they have an effect of 54.3% on interest in using shopeepay e-wallet and the remaining 45.7% is influenced by other variables which is not examined. Keywords: Sales Promotion, Perceived usefulness, Perceived ease of use and Interest in Using e-wallet Shopeepay